Peran Orang Tua Dalam Memotivasi Belajar Peserta Didik Smp/Mts Di Kecamatan Alok Timur: Peran Orang Tua Dalam Memotivasi Belajar Peserta Didik Smp/Mts Di Kecamatan Alok Timur - Mau, Helen Tresiana (Universitas Muslim Buton, 2022)
This study aims to determine the role of parents in motivating the learning of SMP/MTs students in East Alok District. This research was conducted in Kelurahan Nangameting RT 002 and Waioti Village RT 038. This study uses a descriptive qualitative research method with data collection techniques used, namely interview techniques with the number of respondents studied with 68 people, namely 34 students and 34 parents in Nangameting Village and Waioti Village,East Alok District. Based on the results of interviews of parents and students that parents are often and do not accompany, control the time of study and guide students while studying because parents are busy working so that parents are tired and do not have the full time to accompany and control students learning. From the results of interviews with parents and students the obstacles that parents face in motivating learning are economic conditions so that they do not meet the learning needs of participants are fully identified and the availability of time in assisting and controlling students while studying at home. Therefore, the results of this study can be concluded that parents do not always provide motivators, provide guidance, help students during learning difficulties, and parents provide advice to students but not at any time. Because parents are always busy with work.